Financial investment constraints. A panel threshold application to German firm level data - Artur Tarassow (Hamburg University, Department Socioeconomics, 2014)
This paper attempts to test whether financial supply-side shifts explain the low-investment climate of private firms in Germany. The core contention is that a firm's financial position contributes to its access to external finance on credit markets. Special emphasizes is put on small and medium-sized enterprises as these are usually assumed to be more informationally opaque. The application of a non-linear panel threshold model makes it possible to group firms endogenously according to their financial position. Various observable balance sheet indicators such as leverage, interest coverage ratio or measures of solvency are used as potential threshold variables. The firm-level panel dataset covers the period between 2006 and 2012. We find strong evidence for a positive but non-linear nexus between cash flow and fixed investments, suggesting that financially fragile firms rely more heavily on internal funds. Surprisingly, firm size does not seem to be a relevant grouping variable.
More recent version: http://hdl.handle.net/10419/120855
Keywords: C23; D24; E22; E30; G31; 330; Non-linear panel model; Firm investment; Corporate finance; Business cycle; Financial frictions; Credit rationing; Cash flow; Monetary policy